Diagnosability of arrangement graphs with missing edges under the MM* model. Issue 1 (2nd January 2020) - Wang, Shiying; Ma, Xiaolei
Abstract : Diagnosability is an important parameter to measure the fault tolerance of interconnection networks. Arrangement graph A n, k is a generalisation of the star graphs, yet it is more flexible in its size than the star graphs. In this paper, we study the local diagnosability of A n, k, and show that it has the strong local diagnosability property even if there exist ( k − 1 ) ( n − k ) − 1 missing edges in it under the MM* model, and the result is optimal with respect to the number of missing edges. GRAPHICAL ABSTRACT: